An exploratory study to improve reading and comprehending mathematical expressions in braille. (May 2023) - van Leendert, Annemiek; Boonstra, LG; Doorman, Michiel; Drijvers, Paul; van der Steen, Johannes; Pel, Johan
Braille readers read and comprehend mathematical expressions while moving their fingertips over braille characters. The aim of this exploratory study was to investigate the effect of an intervention that teaches braille readers who use a braille display to use finger movements with a focus on the expression's mathematical structure. The finger movements involved movements where the two index fingers are about one or two braille cells apart and movements where the index fingers explore different parts of the expression. We investigated to what extent the intervention supports an interplay between finger movements and the expression's mathematical structure to make the process of calculating the value of an expression easier and to make braille readers more aware of the expression's structure. Three braille readers, respectively in Grades 7, 8, and 11, received the intervention consisting of five individual lessons. During the pre-, post-, and retention test, the braille readers' finger movements were video recorded, as well as the time needed to read and process the mathematical tasks. Four expressions were selected for further analysis. The results show that during the posttest, each braille reader required at least 29% less time to read and process the expressions. The retention test results were even better. Scanpaths indicated that braille readers picked up features of mathematical structures more easily after the intervention. Based on our findings, we recommend that braille readers receive lessons in tactile reading strategies that support the reading and processing of mathematical expressions and equations.